The Effectiveness of Cake App to Teach Speaking - Ema Riska Maulida; Siti Raodatul Warni Mukti; Muhammad Husnu; Ahmad Yusri (CV. ULIL ALBAB CORP, 2024)
The purpose of this study is to introduce Cake App as a medium to improve students' speaking skills. Communicative App for Key English stands for CAKE. Communicative App for Key English can be downloaded for free from AppStore or Google Play, complete with various features to improve speaking and train them with various exercises to pronounce words/phrases/sentences correctly. It comes with a microphone icon that students can use directly to speak according to the audio that has been played. This study is an action research that aims to improve students' speaking skills by using Cake application. This study discusses how Cake application as a learning media can improve students' speaking ability. Data were collected through speaking tests and interviews in a classroom action research. The researcher made three cycles and gave scores for each cycle. In the first cycle, the students' average score was 30 points, the second cycle was 70 points. Cake Application helps students in pronouncing various kinds of words more easily and comprehensively. The results showed that the use of Cake application has provided convenience and benefits for students in improving their English Speaking skills by using Cake application.